PENGARUH SISTEM INFORMASI PEMASARAN DAN STRATEGI PENJUALAN TERHADAP PERSAINGAN PENJUALAN PRODUK PT. BANK AGRIS, TBK MEDAN - Edwin Sugesti (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This study aims to determine the effect of marketing information systems and product sales strategies on product sales competition of PT. Bank Agris, Tbk Medan. This research is a field research with quantitative methodology. Data obtained through questionnaires is distributed to a sample of 97 respondents. A number of populations is 2,958 people consisting of bank customers. The researcher used incidental sampling techniques as a sampling technique. Data analysis was carried out by multiple linear regression analysis approach which included validity and reliability, classic assumption test, hypothesis testing through t and F test, and test the coefficient of determination (R2). The results prove that: Y = 12,623 + 0,359 X1 + 0,355 X2 + e whereas the t test show that the marketing information system variable has a positive and significant effect on product sales competition where t-count 2.350 t-table 1.661 and product sales strategy variables have a positive and significant effect on product sales competition where t-count 2.359 t-table 1.661. While the results of the F test show that F-count 14,631 F-table 3.09 which means that the independent variable (marketing information system and product sales strategy) simultaneously influences the dependent variable (product sales competition). The test results of the coefficient of determination (R2) show that 23.7% of product sales competition at PT. Bank Agris, Tbk Medan is influenced by marketing information system variables and product sales strategies, while the remaining 76.3% is influenced by other variables that are not examined in this study.